DIGITAL MEETS TRADITION: READING PREFERENCES AND ACADEMIC ACHIEVEMENT IN ISLAMIC HIGHER EDUCATION - Jamri Dafrizal; Yuldelasharmi Yuldelasharmi; Zulfitri Zulfitri; Diah Sa'adiah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
The digital transformation era has fundamentally reshaped reading behavioral patterns among university students, particularly within Islamic higher education contexts where traditional literacy practices maintain profound cultural and pedagogical significance alongside emerging digital competencies. This empirical investigation examines reading modality preferences among Islamic Library and Information Science (IPII) students at UIN Sultan Maulana Hasanuddin Banten, analyzing relationships between five distinct reading modalities: traditional print-based reading, digital-mediated reading, academic-focused reading, leisure-oriented reading, and social media consumption patterns. A cross-sectional survey employed a 244-item validated questionnaire administered to 71 IPII students (72.4% response rate, N=98). Statistical analyses included descriptive statistics, Pearson correlations, factor analysis, and cluster analysis using SPSS 28.0. Digital reading demonstrated highest engagement (M = 3.68, SD = 0.52), followed by academic reading (M = 3.61, SD = 0.71) and traditional reading (M = 3.42, SD = 0.63). Strong positive correlations emerged between traditional and academic reading (r = 0.563, p < 0.001). Cluster analysis identified three profiles: digital-oriented readers (40.8%), balanced multimedia readers (32.4%), and traditional-preferenced readers (26.8%). IPII students exhibit complementary rather than competitive relationships between reading modalities, necessitating pedagogical approaches that integrate digital competencies while preserving traditional Islamic scholarly practices.